KEEFEKTIFAN DESAIN MEDIA ROLE PLAYING GAMES BERBASIS ANDROID PADA MATERI REDOKS DAN TATA NAMA SENYAWA (Jurnal Inovasi Pendidikan Kimia, 2020)
Growth of education and technology are related that made teacher must be more creative on educate, one of them is the variation of educational media. This research aims to develop an education games using the Android-based Role Playing Games genres that proper and effective to use in the Redox and Compound Nomenclature. This research refers to ADDIE model. Data collection techniques used method of documentation, tests, and questionnaires. The result of documentation method are students mark that analyzed to gain normality and homogenity of the class that used for experiments. Tests used to measure the classical completeness of student in experimental class with the developed media and control class without it. Questionnaire used to determine responses of respondents to the developed media. The results of the assessment by media experts show that media had scored 44,5 from maximum score 48 and by instructional experts show that media had scored 37 from maximum score 44. Media also said to be effective showed from the class completeness of 84,8% in the experiment class higher than control class that scored 54,3%. Media had very good criteria with percentage of 84,8% showed by students questionnaire and 87,5% showed by teachers questionnaire. Â